STRATEGI PEMASARAN DENGAN PENDEKATAN AHP PADA SMK BUDI UTOMO 1 WAY JEPARA LAMPUNG TIMUR - Amin, Muhammad Yasir; Suhada, Bambang; Sigalingging, Marhaban (SIMPLEX: Journal of Economic Management, 2025)
This research aims to analyze the most appropriate marketing strategy for Budi Utomo 1 Way Jepara East Lampung Vocational School between market development strategy (MDS), product development strategy (PDS), brand image strategy (BIS), and market penetration strategy (MPS) using the approach Analytical Hierarchy Process (AHP). The method used in this research is qualitative. Data collection in this research was interviews, observation, and document study. The data analysis techniques used are data reduction, data presentation, and conclusion drawing. The results of the research show that Budi Utomo 1 Way Jepara Vocational School has implemented a fairly good educational marketing strategy, several programs and services offered can attract the tastes and interests of the community, promotional activities carried out by the school are running quite well and are managed centrally by the foundation and assisted by the headmaster. Based on AHP on the 4 marketing components at Budi Utomo 1 Way Jepara Vocational School, it was found that the best factor component for improving marketing was school accreditation with a priority vector value of 0.35. The best actor component for improving marketing is students with a priority vector value of 0.36. The best objective component for improving marketing is producing quality graduates with a priority vector value of 0.33. The best alternative strategy component to improve marketing at Budi Utomo 1 Way Jepara Vocational School is Product Development Strategy (PDS) with a priority vector value of 0.37.